Secondary Reconstruction of the Zygomaticomaxillary Complex - Aman, Hessah M.; Alenezi, Abdulrahman; Ducic, Yadranko; Reddy, Likith V. (Seminars in Plastic Surgery, 2020)
Zygomaticomaxillary (ZMC) fractures are the second most common facial fractures after nasal bone fractures. The zygoma, with its location and multiple points of articulations, lends itself to both facial structure and esthetics. Secondary ZMC deformities are complications of inadequate primary correction, delayed repair, or lack of repair. Secondary revisions of ZMC aim to correct ZMC displacement and projection and to address orbital discrepancies. Extensive correction involving significant orbital and malar defects requires zygomatic repositioning osteotomies and would greatly benefit from the utilization of virtual surgical planning, intraoperative navigation, and imaging. Minor corrections in malar projection can be corrected by onlay grafting and soft tissue augmentation and resuspension. Isolated or minor orbital corrections can be managed by autogenous or alloplastic material to restore lost orbital volume and anatomy.
Keywords: ZMC; secondary reconstruction; enophthalmos; onlay graft; surgical navigation